Wind–Photovoltaic–Electrolyzer-Underground Hydrogen Storage System for Cost-Effective Seasonal Energy Storage - Torsten Clemens; Martin Hunyadi-Gall; Andreas Lunzer; Vladislav Arekhov; Martin Datler; Albert Gauer (Energies)
Photovoltaic (PV) and wind energy generation result in low greenhouse gas footprints and can supply electricity to the grid or generate hydrogen for various applications, including seasonal energy storage. Designing integrated wind–PV–electrolyzer underground hydrogen storage (UHS) projects is complex due to the interactions between components. Additionally, the capacities of PV and wind relative to the electrolyzer capacity and fluctuating electricity prices must be considered in the project design. To address these challenges, process modelling was applied using cost components and parameters from a project in Austria. The hydrogen storage part was derived from an Austrian hydrocarbon gas field considered for UHS. The results highlight the impact of the renewable energy source (RES) sizing relative to the electrolyzer capacity, the influence of different wind-to-PV ratios, and the benefits of selling electricity and hydrogen. For the case study, the levelized cost of hydrogen (LCOH) is EUR 6.26/kg for a RES-to-electrolyzer capacity ratio of 0.88. Oversizing reduces the LCOH to 2.61 €/kg when including electricity sales revenues, or EUR 4.40/kg when excluding them. Introducing annually fluctuating electricity prices linked to RES generation results in an optimal RES-to-electrolyzer capacity ratio. The RES-to-electrolyzer capacity can be dynamically adjusted in response to market developments. UHS provides seasonal energy storage in areas with mismatches between RES production and consumption. The main cost components are compression, gas conditioning, wells, and cushion gas. For the Austrian project, the levelized cost of underground hydrogen storage (LCHS) is 0.80 €/kg, with facilities contributing EUR 0.33/kg, wells EUR 0.09/kg, cushion gas EUR 0.23/kg, and OPEX EUR 0.16/kg. Overall, the analysis demonstrates the feasibility of integrated RES–hydrogen generation-seasonal energy storage projects in regions like Austria, with systems that can be dynamically adjusted to market conditions.